Increased Platelet Glycoprotein V Levels in Patients with Coronary and Peripheral Atherosclerosis - Blann, A. D.; Lanza, F.; Galajda, P.; Gurney, D.; Moog, S.; Cazenave, J. P.; Lip, G. Y. H. (Thrombosis and Haemostasis, 2001)
As platelet hyperactivity is important in atherosclerosis and smoking, we hypothesized higher levels of soluble platelet membrane glycoprotein V (gpV) in 95 patients with peripheral artery disease (PAD) and 92 with coronary artery disease (CAD) compared to 99 healthy controls, and examined the effects of aspirin and of smoking two cigarettes on soluble gpV and platelet function. Soluble gpV (ELISA) was significantly raised in, but not between, both PAD and CAD patients, compared to controls (p <0.05). In multivariate analysis, systolic blood pressure, smoking and atherosclerosis (all p <0.01) were significant influences on soluble gpV in the whole study cohort. There was a weak correlation between soluble gpV and another platelet marker, soluble P selectin (p = 0.048). Acute smoking in 14 subjects increased platelet aggregability and beta-thromboglobulin, but not soluble gpV: there were no changes in 11 non-smokers. Five days consumption of aspirin (325 mg daily) by 14 subjects did not influence levels of soluble gpV. Our data indicate that soluble gpV may be a useful new marker of platelet activation in atherosclerosis, but may be influenced by smoking status and blood pressure.
Keywords: Platelets; smoking; atherosclerosis